Key factors influencing the outcome of Energy Projects procured using Public Private Partnerships in South Africa - Wimbush Justin (Energy Research Centre, 2019)
Processes required for the procurement of construction projects by the public and private sectors must comply with many requirements and incentives, not least of which is usually the requirement to provide value for money. However, large capital works construction projects, particularly those undertaken by the public sector, have a tendency to over-run both their construction schedules and their budgets. This is amply demonstrated in South Africa by the construction of the Medupi and Kusile coal fired power stations by Eskom, the South African national power utility, which are both running over schedule and are projected to be over budget by 52% and 48% respectively. In contrast, Public Private Partnership contracts between the private sector and the South African government were recently used to construct large, utility scale renewable energy facilities in South Africa, with a total capacity equivalent to that of Medupi power station, on time and on budget. This research study considers the various procurement options in use globally for the construction of capital projects, before looking in detail at the Public Private Partnerships approach for infrastructure procurement, both globally and in the South African context for energy projects. The research study and aims to answer the questions, “What are the key factors that influence the outcome of energy projects procured using public private partnerships in South Africa?” and “What interventions could improve the success rates of projects procured using public private partnership contracts in South Africa?”. A social constructionist epistemology was adopted to guide the research, as the context of the research questions is complex requiring flexible research approaches, able to consider matters such as the perceptions of stakeholders involved in energy projects. The research study makes use of a systematic literature review of international publications, and a survey of individuals working in the South African renewable energy industry. The data was analysed using qualitative content analysis to identify themes, and further coded to identify the factors. The research study aims to contribute to the body of knowledge on the use of the effectiveness of the Public Private Partnerships approach used for the procurement of energy projects in South Africa as there appears to have been little research undertaken in this area to date.